2014
DOI: 10.1177/1934578x1400901102
|View full text |Cite
|
Sign up to set email alerts
|

A New Sesquiterpene Lactone and Other Constituents of Moquiniastrum polymorphum subsp. floccosum (Asteraceae)

Abstract: A new guaianolide, 1S, 3S, 5R, 6S, 7S, 11R-1-hydroxy-11,13-dihydrozaluzanin C (1), was isolated from Moquiniastrum polymorphum subsp. floccosum trunk bark, together with fifteen known compounds, which were identified as 11,13-dihydroglucozaluzanin C (2), 8-hydroxy-11,13-dihydrozaluzanin C (3), zaluzanin C (4), gochnatiolide B (5), ethyl caffeate (6), methyl chlorogenate (7), ethyl chlorogenate (8), methyl 3,5-dicaffeoyl quinate (9), ethyl 3,5-dicaffeoyl quinate (10), methyl 4,5-dicaffeoyl quinate (11), eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…For high-performance liquid chromatography (HPLC), methanol (HPLC grade, Panreac), trifluoroacetic acid (analytical grade, Vetec), and ultra-pure water from a Milli-Q system were used for the eluent preparation. 3,5-O-[E]-Dicaffeoylquinic acid (3,5-CQA), 4,5-O-[E]-dicaffeoylquinic acid (4,5-CQA), and 3,4-O-[E]-dicaffeoylquinic acid (3,4-CQA) were previously isolated and identified by NMR (Strapasson et al 2015) and used as authentic chemical reference compounds.…”
Section: Chemicalsmentioning
confidence: 99%
“…For high-performance liquid chromatography (HPLC), methanol (HPLC grade, Panreac), trifluoroacetic acid (analytical grade, Vetec), and ultra-pure water from a Milli-Q system were used for the eluent preparation. 3,5-O-[E]-Dicaffeoylquinic acid (3,5-CQA), 4,5-O-[E]-dicaffeoylquinic acid (4,5-CQA), and 3,4-O-[E]-dicaffeoylquinic acid (3,4-CQA) were previously isolated and identified by NMR (Strapasson et al 2015) and used as authentic chemical reference compounds.…”
Section: Chemicalsmentioning
confidence: 99%
“…Due to its good resistance to adverse conditions, with a density of 0.76 g cm³, M. polymorphum is mainly used as wood for small rural buildings and fencing. The species, however, also carries pharmacological, ornamental and environmental value (Pessatto et al 2017;Strapasson et al 2017;Corrêa et al 2018;Brandes et al 2019). For example, because of its phenotypic plasticity, it is successfully used in the restoration and rehabilitation of degraded forests (Rossatto and Kolb 2010;Ribeiro and Kolb 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Asteraceae is a family of eudicots characterized by diverse bioactive metabolites, and the Moquiniastrum genus, which belongs to this family, is found in South America and is used in folk medicine for treating respiratory diseases, such as asthma, bronchitis, coughs, and colds. Studies revealed these plants exhibit anti-trypanosomal, antiradical, anti-inflammatory, antispasmodic, antibacterial, cytotoxic, and antioxidant activities [10][11][12][13]. This genus has already been found to contain compounds such as genkwanin, hispidulin, cirsimaritin, and chlorogenic acid derivatives.…”
Section: Introductionmentioning
confidence: 99%